PENGARUH BOBOT KOLONI DAN JENIS PAKAN TERHADAP KUALITAS PUPUK ORGANIK CAIR KOMPOS CACING Lumbricus rubellus (The Effect Of Colony Weight and Feed Type on The Quality Of Liquid Organic Fertilizer Vermicompost Lumbricus rubellus) - A., Jaya,; R., Mulahartani,; Kamilah, Kamilah; B.S., Lautt, (Universitas Palangka Raya, 2018)
ABSTRACTÂ Liquid organic fertilizer is able to provide nutrients from leachate extract (liquid) as a result of changes in worm metabolism, growing media or residual worm feed as a result of the composting process. This study aims to determine the interaction between feed type with worm colony weight as well as the influence of worm weight and type of feed on the quality of L. rubellus compost liquid organic fertilizer. The research was carried out at the experimental field of the Department of Agriculture and in the analytical laboratory of the University of Palangka Raya using completely randomized design (CRD) with 3x3 factorial pattern. The first factor was colony weights of L. rubellus (C1 : 50 g, C2 : 75 g and C3 : 100 g) and the second was types of feed (P0 : control, P1 : green vegetable waste and P2: sedge-grass leaves). The results showed that 100 g worm colony weights with feed from alang-alang leaves produced the highest Nitrogen nutrient (18.33 mg g-1), on phosphorus nutrients the interaction was not significant but had a significant effect from the treatment of feed where the green vegetable waste producedÂ the lowest phosphorus nutrients (85.67 mg g-1), but the treatment without feed (control) and sedge-grass leaves (Imperata cylindica) and the treatment of worm colony weight were not affect on the quality of L. rubellus compost liquid organic fertilizer.Â Keywords : Colony Weight, Feed Type, Liquid Organic Fertilizer, Lumbricus rubellus